Evidence level of nursing care technologies in angioplasty of the lower limbs - Viviane Soares; Juliana Balbinot Reis Girondi; Karina Silveira de Almeida Hammerschmidt; Lucia Nazareth Amante; Darla Lusia Ropelato Fernandez; Luciara Fabiane Sebold (Universidade Federal de Goias, 2016)
The objective of this study was to describe the scientific work on nursing care technologies to adult patients undergoing angioplasty of the lower limbs. Systematic review of the literature followed the electronic databases: LILACS, PubMed, Web of Science, SciELO, and Google Scholar. Twelve articles were analyzed and classified according to the levels of evidence. All qualitative studies were classified with a low degree of recommendation, and as for the quantitative studies only one showed a high degree of recommendation. The research showed studies with the lowest level of scientific evidence, aside from a lack of research and poor scientific background in which nursing preoperative care to patients undergoing angioplasty of the lower limbs have been developed. Consequently, there is a lack of information and hence poor training, culminating in unpreparedness in providing care to patients, and in understanding and leading this high complexity service according to the safety principles of patient care.